Comparison of Three Independent Methods of Cephalexin Determination by Means of Potassium Caroate - Ye Blazheyevskiy Mykola; Yu Serdiukova Yuliia
ABSTRACT Aims: Three different assays for the quantity determination of Cephalexin in pure substance were developed and compared using potassium caroate as analytical reagent. Materials and Methods: Cephalexin pure substance was used and analytical reaction by means of KHSO5 as an oxidant was studied. Voltammetric, kinetic-spectrophotometric and iodometric methods were developed and validated. Results: The chemical reaction is finished with formation of the S-oxide of Cephalexin in the iodometric and voltammetric methods and the S-oxide hydrolysis product in the kinetic-spectrophotometric method. The reaction finishes in 1 min (observation time). The methods have been validated and good results including precision, accuracy and recovery were obtained. The recovery percent ranged from 98.7 to 101.4%, RSD from 1.42 to 3.0%. The methods proposed are linear in a wide range: voltammetry 2-45 μg mL-1, kinetic-spectrophotometry 1-16 μg mL-1, and iodometry 0.05-0.35 mg mL-1. LOD and LOQ were calculated. The kinetic-spectrophotometric method is the most sensitive (LOQ=1.0 μg mL-1). Conclusions: The methods proposed are rapid, simple and inexpensive and could be applied to pharmaceutical preparation.